EKONOMI HIJAU SEBAGAI SOLUSI KEBERLANJUTAN: TINJAUAN LITERATUR DARI PERSPEKTIF SOSIAL DAN EKONOMI - Loso Judijanto; Nurussama (JOURNAL OF COMMUNITY DEDICATION, 2024)
The green economy as a sustainability solution from a social and economic perspective explores the potential of transitioning towards a green economy as an answer to global environmental challenges. The main focus of the green economy is to reduce carbon emissions, improve resource use efficiency, and protect biodiversity with the aim of achieving a balance between economic growth and environmental protection. From a social perspective, a green economy is believed to improve people's welfare through the creation of new jobs and improved access to resources. Meanwhile, from an economic perspective, while it requires a large initial investment, the shift offers cost efficiencies and opens up new opportunities for technological and market innovation. In conclusion, a green economy can be a key strategy to achieve inclusive and environmentally sustainable development.